The Response of Plant and Soil Properties of Alpine Grassland to Long-Term Exclosure in the Northeastern Qinghai–Tibetan Plateau - Huang, Cuihua; Peng, Fei; You, Quangang; Liao, Jie; Duan, Hanchen; Wang, Tao; Xue, Xian (Frontiers in Environmental Science, 2020)
Currently, grazing exclosure is one of the most important grassland management measures for restoring all types of degraded alpine grassland in the Qinghai–Tibetan Plateau (QTP). The most widely distributed grassland ecosystems across the northeastern QTP are the alpine meadow (AM), alpine meadow steppe (AMS), and alpine steppe (AS). However, whether the impacts of fencing on vegetation characteristics and soil properties vary among different grassland types remains poorly understood despite that numerous individual studies have been conducted. This study investigated the vegetation characteristics and soil properties in fenced and grazed AM, AMS, and AS in the northeastern QTP. Grazing exclosure significantly increased the vegetation coverage and Shannon–Wiener diversity index in all the three grasslands. Plant species richness was significantly increased in AM, but there were no significant changes in AMS and AS. Aboveground biomass was significantly increased in AMS and AS but not significant in AM. Increase in the percentage of high-quality forage grasses was only observed in AMS. Fencing significantly decreased the soil bulk density (BD) and significantly increased soil organic carbon (SOC) and total nitrogen at a depth of 0–50 cm in AMS and AS but had no effect in AM. Our results indicate that the use of fencing for restoring degraded AM might not achieve the same expected results as in AS and AMS on the QTP.